Risk factors predicting mmii asymmetry in ultimate frisbee players (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2023)
Introduction: The different studies focus the research on neuromuscular asymmetries determining extrinsic and intrinsic factors, compared to previous studies and documentary evidence of neuromuscular asymmetries in the lower limbs (MMII) in team sports, no previous studies on asymmetries neuromuscular disorders in Ultimate Frisbee players have been found. Objetive: to determine predicting risk factors of MMII asymmetry in Ultimate Frisbee players Methods:. correlational descriptive study, with a multivariate phase; performed on 133 athletes aged 15 to 20 belonging to Ultimate Frisbee clubs and leagues; The techniques were the observation based on the assessment of asymmetry using the Hop Test, and the observation of established physical capacities, formats/documents of: consent and informed assent, registration survey for sociodemographic data, sports practice, and functional evaluation. Results: It is evident that extrinsic factors such as (field, footwear, and preventive work) are essential for the symmetrical development of the athlete. Therefore, there is a significant association between the symmetry of MMII and post-training recovery variables (p=0,009) and the execution of preventive programs (p=0.02), which reflects the importance of implementing post-workout or post-competition recovery programs in order to reduce the risk of injury. Conclusions: The instrument applied (hop test) made it possible to establish a monitoring and control protocol in sports processes to determine risk factors in Ultimate Frisbee.
Keywords: Athletic Injuries; Lower Extremity; Athletes